Stand structure influences understory plant diversity through soil factors: three afforestation types of Masson’s pine in the upper Yangtze River, China - Xiang, Yongqi; Lyu, Qian; Yang, Huiqin; Yin, Biran; Tang, Zhiren; Hou, Guirong; Chen, Gang; Zhao, Kuangji; Chen, Yuqin; Fan, Chuan; Li, Xianwei (Frontiers in Plant Science, 2025)
PurposeIn general, mixed forests have the potential to enhance understory plant diversity. However, the effects of stand spatial structure formed by different types of mixed afforestation on understory plants communities are still not clear.MethodsTo answer these questions, we examined the stand spatial structure’s impact on soil (nitrogen, phosphrous, potassium, etc.) and understory plant communities (diversity indexes, ecological niche width and resource overlap of shrub and herb) in three types of Pinus massoniana afforestation: a monoculture (MPF), a mixed forest with Cunninghamia lanceolata (MCLMF), and a mixed forest with Liquidambar formosana (MLMF).ResultsMCLMF substantially increased diversity and ecological niche width for understory shrubs and herbs, steered understory plants toward resource utilization generalism. MLMF enhanced shrub diversity by reducing dominant species ratios. In terms of stand structure, MCLMF significantly increased the opening degree (O), mingling index (M), and competition index (CI), while MLMF decreased CI but increased M. Redundancy analysis indicated that the opening degree explained 52.47% of the variation in shrub diversity and 42.51% in herb diversity, and CI explained 24.57% of the shrub diversity variation. Soil pH, total nitrogen, and available potassium were significantly enhanced after mixed afforestation. The indices O, CI, and M indirectly affect the diversity of understory plants through soil properties, such as temperature, moisture, available nutrients (e.g., nitrogen, phosphorous, and potassium), organic carbon, and pH.ConclusionsStand spatial structure significantly shapes understory plant community structure through soil mediation, demonstrating its role in enhancing artificial forest quality and stability in ecologically sensitive areas.